Blood pressure regulation by CD4+ lymphocytes expressing choline acetyltransferase - Olofsson, Peder S; Steinberg, Benjamin E; Sobbi, Roozbeh; Cox, Maureen A; Ahmed, Mohamed N; Oswald, Michaela; Szekeres, Ferenc; Hanes, William M; Introini, Andrea; Liu, Shu Fang; Holodick, Nichol E; Rothstein, Thomas L; et al. (Nature biotechnology, 2016)
A CD4 T-cell population expressing choline acetyltransferase is shown to contribute to blood pressure regulation. Blood pressure regulation is known to be maintained by a neuro-endocrine circuit, but whether immune cells contribute to blood pressure homeostasis has not been determined. We previously showed that CD4 + T lymphocytes that express choline acetyltransferase (ChAT), which catalyzes the synthesis of the vasorelaxant acetylcholine, relay neural signals 1 . Here we show that these CD4 + CD44 hi CD62L lo T helper cells by gene expression are a distinct T-cell population defined by ChAT (CD4 T ChAT ). Mice lacking ChAT expression in CD4 + cells have elevated arterial blood pressure, compared to littermate controls. Jurkat T cells overexpressing ChAT (JT ChAT ) decreased blood pressure when infused into mice. Co-incubation of JT ChAT and endothelial cells increased endothelial cell levels of phosphorylated endothelial nitric oxide synthase, and of nitrates and nitrites in conditioned media, indicating increased release of the potent vasorelaxant nitric oxide. The isolation and characterization of CD4 T ChAT cells will enable analysis of the role of these cells in hypotension and hypertension, and may suggest novel therapeutic strategies by targeting cell-mediated vasorelaxation.